KERJASAMA PEMERINTAH PROVINSI SULAWESI SELATAN DAN PREFEKTUR EHIME DALAM PENINGKATAN PRODUKSI IKAN TUNA - Muhammad Fikri Amra; Howard Benyamin L (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2023)
This research was conducted to explain how the cooperation between South Sulawesi Province and Japan's Ehime Prefecture is a form of sister province cooperation where this inter-regional cooperation aims to provide options for regional development. This study uses a qualitative method with a descriptive approach that is built on the theory of Paradiplomacy and the concept of Sister Province based on the analyst's explanation given by Takdir Ali Mukti who assumes that Paradiplomacy refers to the behavior and capacity of conducting foreign relations with foreign parties carried out by sub-state entities, in the context of their specific interests. The concept of sister province cooperation is the solution taken by the South Sulawesi Provincial Government in cooperation with Japan's Ehime Prefecture. In this collaboration, the Provincial Government of South Sulawesi cooperates in the development of several fields where one of the most interested in Japan is cooperation in the field of marine product cultivation in which the type of commodity is tuna. The solution taken by the South Sulawesi government by using the sister province cooperation channel found variables that encourage South Sulawesi to find strategies used in developing tuna fish production.